Behavior of Pregnant Women in Using Posyandu to Check ANC (Anteatal Care) at Eka Sriwahyuni Clinic Medan 2023 - Kamaliah (International Journal of Public Health Excellence (IJPHE), 2024)
Antenatal care is crucial for the survival of both the mother and fetus during pregnancy and childbirth. ANC services consist of observation, education, and treatment for pregnant women. The objective of this research is to identify the factors that affect maternal compliance with Antenatal Care Visits at the Eka Sriwahyuni Clinic in Medan. The research design is analytical observation. The study population comprised of 17 pregnant women who attended Posyandu Klinik Eka Sriwahyuni Medan. The sample was selected using total sampling technique. Data was collected through a questionnaire and analyzed using the Chi Square test (p value <0.05). The study found that 64.7% of respondents had sufficient knowledge, 70.6% had attitudes in the sufficient category, and 52.9% had husband support in the sufficient and partial categories. Additionally, 64.7% of respondents had good compliance with visits. The chi-square test results indicate a relationship between knowledge, attitudes, and husband's support factors and compliance with Antenatal Care Visits at the Eka Sriwahyuni Clinic in Medan. To further explore factors that may influence ANC visit compliance, future researchers should consider economic factors and distance from health facilities. This research involved visiting respondents individually, which may have been less effective.